2022
DOI: 10.1155/2022/9142489
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Thromboelastography Parameters in Urosepsis: A Retrospective Study

Abstract: Thromboelastography (TEG) is usually used to monitor coagulation disorder clinically. It is unclear whether TEG has association with urosepsis and sepsis-induced coagulopathy (SIC). The purpose of this study was to investigate the clinical significance of TEG parameters in urosepsis. 90 patients who were admitted to the Emergency Ward and Emergency Intensive Care Unit (EICU) of Ren Ji Hospital affiliated to Shanghai Jiao Tong University School of Medicine due to urinary infection from February 2014 to February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%